Parallels and Disparities in Nātyaśāstra and Poetics - Kandel, Churamoni (Kaumodaki: Journal of Multidisciplinary Studies, 2023)
This paper interprets the parallels and disparities in Nātyaśāstra and Poetics. The former treatise of drama is set by Bharatmuni from the East; the latter by Aristotle from the West. Hence, these dramaturgies form the bases for the eastern and western plays, respectively. Despite the time and spatial differences between the two, they contain similarities as well as differences. They share the common dramatic elements like gestures, dance and music; rhythm, poet and mimesis; plot, sub-plot and supernatural elements; art and imitation; rasa (evocation of emotion) and catharsis. Likewise, they contain the elements of disparities like language-style differences, semiotic and semantics, abhinaya (acting) and art, the absence of tragedy in the former, Rasa to the former and plot and character to the latter. This researcher explores how these elements of parallels and disparities in the two theories of dramas fit to the eastern and western plays, despite their spatial and temporal gaps. This research is exploratory and explanatory.